Relasi Gender dalam Pengelolaan Pariwisata Pantai Mutiara di Desa Tasikmadu Kecamatan Watulimo Kabupaten Trenggalek - Yuga Nanta, Luki Ricard; Utami, Diyah (Paradigma, 2023)
This study aims to identify the role of women in the management of pearl beach tourism in Tasikmadu Village, Watulimo District, Trenggalek Regency and analyze the form of gender relations in pearl beach tourism management in Tasikmadu Village, Watulimo District, Trenggalek Regency. Research method with a qualitative approach and using the perspective of liberal feminism Naomi Wolf. The results of this study show that the division of labor in the management of Pearl Beach tourism between men and women has not been balanced. In addition to the dominance of men, it is also caused by women, Pearl Beach tourism managers are more passive in every activity. Some cultural views that have been believed by the community often make women seem to be cornered, causing gender inequality in the management of Pearl Beach tourism. In the division of labor of the Pearl Beach tourism management group, many men occupy strategic positions. Gender relations that occur make men get an important role while women act more as supporters than men. Keywords: Gender Relations, Management, Mutiara Beach